UNDERSTANDING THE ROLE OF JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Irawan, Vina Devi Yekti; Wahono, Puji; Adha, Maulana Amirul (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
The success and effectiveness of a company really depends on the quality of the human resources the company has. The behavior expected by the company is not only working according to company standards (in role) but also behaving beyond company standards (extra role). This research aims to examine job satisfaction, organizational commitment and Organizational Citizenship Behavior (OCB), as well as to determine the influence between job satisfaction, organizational commitment and Organizational Citizenship Behavior. The research method used in this research is a quantitative method. The data obtained was primary data through survey data collection methods using proportional random sampling techniques. The population used in this research was 162 employees with a total of 115 samples calculated based on the Slovin formula. The data was processed using SPSS version 26 software by carrying out correlation tests and multiple regression analysis. The results of this research show that job satisfaction and organizational commitment have a positive and significant effect on Organizational Citizenship Behavior both partially and simultaneously.